2020
DOI: 10.1108/ijphm-09-2019-0064
|View full text |Cite
|
Sign up to set email alerts
|

Customer relationship management and patient satisfaction and loyalty in selected hospitals in Ghana

Abstract: Purpose This paper aims to examine the effect of customer relationship management (CRM) on patient satisfaction and patient loyalty, controlling for other socio-demographic characteristics. Design/methodology/approach The study used a two-stage sampling process and structured questionnaires to collect data from 788 patients from three health facilities (public, quasi-public and private) in Greater Accra, Ghana. The data collected was analyzed using descriptive statistics and regression via the partial least … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 47 publications
2
14
0
2
Order By: Relevance
“… 24 Satisfaction can be improved through variables such as reliability, empathy, and responsiveness, and the loyalty of patients will be strongly affected by satisfaction. 25 Abekah-Nkrumah et al 26 found that the ownership of health facility will not directly affect PS and PL.…”
Section: Literature Reviewmentioning
confidence: 99%
“… 24 Satisfaction can be improved through variables such as reliability, empathy, and responsiveness, and the loyalty of patients will be strongly affected by satisfaction. 25 Abekah-Nkrumah et al 26 found that the ownership of health facility will not directly affect PS and PL.…”
Section: Literature Reviewmentioning
confidence: 99%
“…It is because customers’ satisfaction positively impacts their loyalty, sales and other attitudinal and behavioural consequences. Therefore, it is necessary to obtain and use critical information about patients’ needs, expectations and choices that affect their satisfaction (Abekah-Nkrumah et al , 2021).…”
Section: Literature Review On Perceived Quality and Patients’ Satisfa...mentioning
confidence: 99%
“…Oleh karena itu, menjadi penting bahwa bisnis tidak hanya mencari konsumen baru tetapi yang lebih penting ialah untuk mengatur stategi dan menerapkan cara untuk bisa mempertahankan konsumen lama yang sudah sering berlangganan sebelumnya. Dasar untuk menjaga pelanggan lama ialah karena lebih sulit mempertahankan daripada mendapatkan konsumen baru (Abekah-Nkrumah et al, 2020), sebagian besar bisnis berkomitmen untuk membangun hubungan dengan konsumen yang baik, dan menunjukkan layanan konsumen yang sangat baik (Alam et al, 2021). Selain itu, adanya kepercayaan juga sangat penting dalam menjalin hubungan dengan konsumen.…”
Section: Pendahuluanunclassified
“…Customer Trust adalah inti dari setiap transaksi dan juga merupakan faktor pendorong yang meningkatkan hubungan dengan konsumen. Sehingga hal tersebut dapat mengurangi kecenderungan konsumen untuk beralih ke pesaing, berbagai perusahaan telah menjadikan manajemen hubungan pelanggan (CRM) sebagai fokus utama perbaikan budaya organisasi (Abekah-Nkrumah et al, 2020;Choi et al, 2013). Didalam CRM terdapat komponen yang berpusat pada konsumen yaitu, Customer Orientation, Customer Knowledge, Customer Engagement, dan Customer Advocacy (Alam et al, 2021).…”
Section: Pendahuluanunclassified